Design of a storage mechanism designed for a railway vehicles producer - Blatnický, Miroslav; Dižo, Ján; Falendysh, Anatoliy (International Journal of Engineering and Technology, 2018)
In this article the engineering design and strength analyses of a storage mechanism are presented. The handling device is intended to be placed in a warehouse and it will serve as a storage mechanism for longer metallurgical material in a railway vehicle manufacturing company. Stored material will be used for creation of some parts of railway wagons. It will allow to storage material in several levels in shelves. To meet requirements for manual control of the pull-out mechanism it will be necessary to design a pull-out mechanism with the sufficiently large transmission ratio in order to handle a shelf block weighing up to given load. Consequently, there are conducted the numeric strength analysis of steel construction which has to safely carry the total load of ten shelves.